Financial Stability of Islamic and Conventional Banks of the MENA Region: Post and Pre-Crisis of CAMELS Framework - Fadoua, Joudar; Brahim, Dinar (International Journal of Islamic Banking and Finance Research, 2020)
The present study provides new empirical evidence of bank stability measure for 12 Islamic and conventional banks in the MENA region, for a period from 2005 to 2014. The most known method of measuring bank stability is using CAMELS variables; it was adopted by multiple central banks. After calculating financial ratios for the CAMELS framework, we calculate the average for each variable for the two types of banks, for three periods: Pre-crisis 2005-2006, Subprime Crisis 2007-2008, and Post-Crisis 2009-2014, to examine the effect of the crisis on the soundness of Islamic and conventional banks.